Curricular internship report developed at snowboard coach in Arinsal, Andorra - Martins, André Gabriel (2020)
This Internship Report is the final work of the Curricular Internship program, which is the curricular unit of second year of the Master’s Degree in Nature Sports, in Superior School of Sports and Leisure (Polytechnic Institute of Viana do Castelo). Therefore, this work aims to report the learnings and activities of the Internship that took place in Arinsal, Andorra, with Snowboard Coach - a company that is specialized in Snowboard Instructors’ training and assessment. The Internship Plan consisted on completing the Level 1 Snowboard Instructor course from the British Association of Snowsports Instructors (BASI), in order to be eligible to be trained and assessed by Snowboard Coach for the BASI Level 2 Snowboard Instructor course. Except for some details, the plan was followed and I have completed the BASI Level 1 and Level 2 Snowboard instructor courses with success. I became not only a Snowboard Instructor, but a more complete and knowledgeable Nature Sports professional in what concerns the mountain environment with winter type conditions. Additionally, an Investigation regarding Injuries among Advanced British Snowboarders was conducted during the Internship period, in order to add to the scientific value of this work and put in practice all the methodology learnings from previous years of investigation practices. A retrospective questionnaire was given to all of the BASI Level 2 trainees, and a prospective analysis was made during the season. Knee and rib injuries were the most common (N=5), and the most reported injury type was fractures (N=9). The results lead to the conclusion that injury profiles differ between advanced and beginner Snowboarders, and that further research is needed in order to validate the correlation between the riders’ level of expertise and their injury patterns.